2014
DOI: 10.1002/chir.22337
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Chirality and Prochirality at Air/R‐(+)‐ and S‐(–)‐Limonene Interfaces: Spectral Signatures With Interference Chiral Sum‐Frequency Generation Vibrational Spectroscopy

Abstract: We report in this work detailed measurements of the chiral and achiral sum-frequency vibrational spectra in the C-H stretching vibration region (2800-3050 cm(-1)) of the air/liquid interfaces of R-(+)-limonene and S-(-)-limonene, using the recently developed high-resolution broadband sum-frequency generation vibrational spectroscopy (HR-BB-SFG-VS). The achiral SFG spectra of R-limonene and S-limonene, as well as the RS racemic mixture (50/50 equal amount mixture), show that the corresponding molecular groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 67 publications
(294 reference statements)
1
44
1
Order By: Relevance
“…The results helped to develop the concept and experimental methodology to study intrinsic chirality and prochirality of chiral molecules on surfaces. It was also found that the two limonene enantiomers are actually not mirror image to each other on the liquid surfaces [90]. Figure 5 HR-BB-SFG-VS resolves two closely overlapping peaks in the 2920 cm -1 peak of the air/DMSO interface.…”
Section: Figure 4 Presents the Comparison Of The Sfg-vs Spectra Of Thmentioning
confidence: 95%
See 4 more Smart Citations
“…The results helped to develop the concept and experimental methodology to study intrinsic chirality and prochirality of chiral molecules on surfaces. It was also found that the two limonene enantiomers are actually not mirror image to each other on the liquid surfaces [90]. Figure 5 HR-BB-SFG-VS resolves two closely overlapping peaks in the 2920 cm -1 peak of the air/DMSO interface.…”
Section: Figure 4 Presents the Comparison Of The Sfg-vs Spectra Of Thmentioning
confidence: 95%
“…One recent experiment with the HR-BB-SFG-VS clearly showed that the chiral and achiral SFG-VS spectra of the R-(+)-limonene and S-(-)-limonene liquid surfaces [90] are both significantly different from the chiral spectra in the limonene bulk liquid [210]. This study not only provided a clear demonstration of the surface-selectivity of the chiral SFG-VS, but also presented a detailed analysis of the intrinsic chirality and orientational (prochiral) chirality contributions in the observed SFG signal [90].The relative phases of each spectral peaks from the R-(+)-limonene and S-(-)-limonene liquid surfaces can be obtained by fitting the HR-BB-SFG-VS [90]. These results are consistent with the direct phase-resolved measurement [207] and are with much better spectral accuracy and better resolved peaks.…”
Section: Surface Selectivity Of Chiral Sfg-vsmentioning
confidence: 99%
See 3 more Smart Citations